Analysis of Stunting among Toddlers at Mauk Health Centre Tangerang Regency - Bunga Tiara Carolin; Jenny Anna Siauta; Nur Amamah; Shinta Novelia (KHD-Production, 2021)
Stunting is one of the problems that hinders human development globally. In Indonesia, the incidence of stunting is around 30.8%, Banten Province 36.9% and in Tangerang Regency 38% where this is still far from the target set by WHO, which is 20%. The objective of this study is to identify the analysis of stunting among toddler in Mauk Public Health Center Tangerang District. This was an analytical survey with a case control design. The sample of this study was 132 people consisting of 66 cases and 66 control groups. Quota sampling sampling technique. The research instrument used a questionnaire. Data analysis used chi-square test. The results show that majority of respondents who did not experience stunting was 84.2%, good knowledge of the mother was 55.3%, the mother's height was not short 64.4%, not given exclusive breastfeeding was 51.5%, did not experience LBW was 72.7%, the small number of family members was 57.6%, and a low family income was 64.4%. The results of the bivariate analysis obtained knowledge (p = 0,000), history of exclusive breastfeeding (p = 0,000), number of family members (p = 0,000), family income (p = 0.029), and history of LBW (p = 0.079). The variable most associated with stunting in children under five mong toddlers was maternal height (OR = 6.00). Therefore, it is hoped that health workers will improve the MCH, Family Planning and Nutrition programs to be better in the future, with more emphasis on the stunting locus program (special stunting locations), by increasing the fulfillment of balanced nutrition during the first 1000 days of life.